Kocher-Debre-Semelaigne Syndrome: Hypothyroid Muscular Pseudohypertrophy—A Rare Report of Two Cases - Chandan Shaw; Prachi Shaw (Case Reports in Endocrinology)
Kocher-Debre-Semelaigne syndrome (KDSS) is a rare association of muscular pseudohypertrophy and long-standing moderate-to-severe hypothyroidism in the pediatric age group. It may be confused with primary muscle disorders, lest one is cautious enough to investigate for hypothyroidism. The striking clinical features, availability of a simple treatment and a good prognosis for the condition makes it worthwhile to report the case so that all practitioners be aware of the condition and its management.